2020
DOI: 10.1371/journal.pmed.1003350
|View full text |Cite
|
Sign up to set email alerts
|

Midwifery continuity of care versus standard maternity care for women at increased risk of preterm birth: A hybrid implementation–effectiveness, randomised controlled pilot trial in the UK

Abstract: Background Midwifery continuity of care is the only health system intervention shown to reduce preterm birth (PTB) and improve perinatal survival, but no trial evidence exists for women with identified risk factors for PTB. We aimed to assess feasibility, fidelity, and clinical outcomes of a model of midwifery continuity of care linked with a specialist obstetric clinic for women considered at increased risk for PTB. Methods and findings We conducted a hybrid implementation-effectiveness, randomised, controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 15 publications
1
47
0
Order By: Relevance
“…Interview data came from a less diverse demographic sample compared to the survey data and this possibly limits richness and breath in the data, particularly for some sub-groups of women. The main pilot trial included a highrisk population with more than one quarter of women in both groups having one or more preexisting medical conditions and multiple obstetric and social risk factors for PTB [14]. Since people who are socially disadvantaged and have complex needs, and those from ethnic minority groups are less likely to engage in research follow up [47], further investigations should focus on community participatory research working in partnership with women with more complex needs who have multiple clinical and social risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interview data came from a less diverse demographic sample compared to the survey data and this possibly limits richness and breath in the data, particularly for some sub-groups of women. The main pilot trial included a highrisk population with more than one quarter of women in both groups having one or more preexisting medical conditions and multiple obstetric and social risk factors for PTB [14]. Since people who are socially disadvantaged and have complex needs, and those from ethnic minority groups are less likely to engage in research follow up [47], further investigations should focus on community participatory research working in partnership with women with more complex needs who have multiple clinical and social risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the first pilot randomised controlled trial to evaluate a model of midwifery continuity of care linked with a specialist obstetric clinic for women at increased risk for PTB were recently published [14]. When assessing feasibility, fidelity and clinical outcomes, authors found that it was feasible to set up and maintain fidelity to the model indicating that a full scale RCT is possible, but the model did not improve the clinical composite outcome of appropriate and timely interventions for the prevention and/or management of preterm labour and birth, in this setting, for this very high-risk population group.…”
Section: Introductionmentioning
confidence: 99%
“…Skin-to-skin contact, sometimes referred to as 'kangaroo care', can be defined as 'placing a naked infant onto the bare chest of the mother' [100] the benefits of which include improved adaptation to extrauterine life, stimulation of the digestive system and hormone release leading to improved feeding, protection against infection, reduced cortisol levels, and parent-infant bonding [100][101][102][103]. A recently published trial of a specialist continuity model of care for women at risk of preterm birth found those women randomised to the intervention were significantly more likely to have skin-to-skin contact after birth and to have it for a longer time [104]. Although the underlying mechanisms for these outcomes remain unclear and warrant further research, the phenomenon could be explained using Lipsky's [105] street level bureaucracy theory in that when midwives know women and are invested in them and their outcomes, they are more likely to provide gold standard practice.…”
Section: Plos Onementioning
confidence: 99%
“…This is in line with our findings from the pregnancy domain of the PCQ Personal treatment, which contains items related to the relationship with the midwife and perceived involvement in the decision-making process, rated higher in the intervention group. In the previous studies [18,19,49,50], satisfaction was measured in midwifery continuity of care models, where known midwives provide continuity of care throughout the childbearing experience from antenatal intrapartum and postpartum care [18,19,55] for women at both high and low risk. The ChroPreg intervention included only continuity of care provided by a known specialized midwife throughout all antenatal and postnatal consultations but not intrapartum, which may explain why we found no difference in satisfaction with care during birth.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%